How Financial Literacy Influences Budgeting, Investment, and Savings Behaviors - S, Dheepiga; N, Sivakumar (International Research Journal of Business Studies, 2025)
This research plans to analyze the interrelationships among financial literacy, budgeting behavior, investment behavior, savings behavior, and financial confidence. It seeks to understand how financial literacy influences individuals' financial behaviors and to assess the potential impacts on their overall financial well-being. A quantitative research methodology was implied, using a cross-sectional study method to collect data from 100 respondents. The connection between the constructs was evaluated through data analysis using Structural Equation Modeling (SEM) with Smart PLS. The results indicated a direct and positive connection between financial literacy and both budgeting behavior and investment behavior and, a negative and a connection that is statistically insignificant between budgeting behavior and savings behavior. This paper highlights the value of financial literacy in enhancing budgeting and investment behaviors. They suggest that financial education programs should address both the practical and emotional aspects of financial management, particularly focusing on fostering financial confidence.